2013
DOI: 10.3390/ijms14059379
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Melatonin: A Novel Therapy against Perinatal Hypoxia-Ischemia

Abstract: One of the most common causes of mortality and morbidity in children is perinatal hypoxia-ischemia (HI). In spite of the advances in neonatology, its incidence is not diminishing, generating a pediatric population that will require an extended amount of chronic care throughout their lifetime. For this reason, new and more effective neuroprotective strategies are urgently required, in order to minimize as much as possible the neurological consequences of this encephalopathy. In this sense, interest has grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 128 publications
1
66
0
4
Order By: Relevance
“…It has been well-documented, as discussed above, that melatonin and resveratrol both exert neuroprotective activity against cognitive deficits via the inhibition of elevated proinflammatory cytokines. It has been shown that melatonin and resveratrol inhibit NF-κB activation and restrain microglia activation, which further reduces the production of proinflammatory cytokines [63][64][65] . In our study, we found that melatonin and resveratrol inhibited the elevated proinflammatory cytokines in the hippocampus of BCCAO-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented, as discussed above, that melatonin and resveratrol both exert neuroprotective activity against cognitive deficits via the inhibition of elevated proinflammatory cytokines. It has been shown that melatonin and resveratrol inhibit NF-κB activation and restrain microglia activation, which further reduces the production of proinflammatory cytokines [63][64][65] . In our study, we found that melatonin and resveratrol inhibited the elevated proinflammatory cytokines in the hippocampus of BCCAO-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…We queried whether this effect was mediated via the antiapoptotic actions of MLT as documented under other pathophysiological conditions. MLT is shown to prevent cytochrome c release, reduce or inhibit caspase-1 and caspase-3 activation, and increase the expression of the antiapoptotic proteins Bcl-2 and Bcl-xL [51,52] . In sheep, MLT attenuates cell death in the fetal brain following intrauterine asphyxia mid-gestation [9] and at full term [6] .…”
Section: Discussionmentioning
confidence: 99%
“…19 Finally, melatonin not only has significant anti-apoptotic activity which mainly targets the mitochondria, but also enhances several cell rescue pathways. 12 Melatonin is an attractive agent for neuroprotection as it freely crosses the placenta and the blood-brain barrier. It protects the brain of asphyxiated animals when used alone 20 or in combination with therapeutic hypothermia.…”
Section: Introductionmentioning
confidence: 99%
“…11 Melatonin has antioxidant, anti-inflammatory and antiapoptotic properties. 12 As an antioxidant, it directly neutralizes reactive oxygen species and reactive nitrogen species including nitric oxide (NO). It also acts indirectly by stimulating both antioxidant enzyme activity and their cellular mRNA concentrations, including superoxide dismutase (SOD), glutathione peroxidase and glutathione reductase.…”
Section: Introductionmentioning
confidence: 99%